Students' Speaking Performance in Simulated Company Profile and Personal Branding Video Projects: A Case Study of IT Students (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2026)
This study examined the speaking performance of IT students in simulated video-based tasks, namely company profile presentations and personal branding videos. The research was conducted as a qualitative case study involving 38 students. Data were collected from students’ video recordings and analyzed using a speaking performance rubric covering fluency, pronunciation, vocabulary use, grammar, and content organization. The findings showed that students achieved higher, more consistent performance on the simulated company profile task, with an overall average score of 3.6, compared to 3.0 on the personal branding task. In the individual task, only 10 of 38 students demonstrated confident, fluent speech. The results indicated that group-based tasks supported fluency and organization, while individual tasks required greater independence and revealed varied speaking abilities. It was concluded that combining collaborative and individual video-based tasks provided balanced opportunities for developing students’ speaking competence.